Diversity in boardroom and debt financing: A case from China - Sun, Xinbo; Ahmad, Muneeb; Tahir, Kamran; Zafar, Hammad (Frontiers in Psychology, 2022)
The study aims to explore the role of gender diversity in debt financing choices among Chinese listed firms. The study used the Chinese listed firm's data from 1991 to 2022 from the Chinese Stock Market return. The study used the fixed effect regression analysis and revealed that gender diversity positively affects debt financing among Chinese firms. Additionally, mass theory results suggested that at least three females on the board significantly influence firms. It served as the voice of gender diversity to influence the board's decisions regarding debt financing. The study has several theoretical and practical implications. This study will enlighten the Chinese boardroom dynamics by reassuring them to add more females to diversity policies. It will benefit future studies on boardroom activities and debt financing in emerging economies. It will be practical guidance for the Chinese policymakers, governing authorities, and corporate executives. The study stresses the need for significant diversity on the board rather than one female presence on the board. Secondly, this study contradicts the stereotype perception that females are not making risky decisions.